PENGEMBANGAN KARIR TUTOR KESETARAAN DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Yolanda Putri; Jaspar Jas; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the career development of equality tutors in the Learning Activities Studio (SKB) Pekanbaru City. This research uses descriptive qualitative paradigm approach. The subject of this research will be determined based on purposive sampling, there are 3 (three) informants in this study. Data collection is done by observation (observation), documentation, in-depth interviews (indept interviews), data analysis is done by: data reduction (data reduction); data exposure (data display); and conclusion drawing and verification (conclusion drawing / verifying). The results of the study show: 1) Equal equivalency tutors implement tutor career development, from tutors' indicators participating in education and training in the LCS, attending seminars in the LCS, attending workshops, following promotions. 2) supporting factors for tutor career development are the SKB equality tutors who always try to participate in various training activities, seminars, workshops and promotions to support their careers in the world of work. While the inhibiting factors are some tutors who are difficult to attend in participating in karri development activities such as seminars, workshops, training. 3) The impact of career development on equality tutors at Pekanbaru City Learning Centers (SKB), where so far the SKB equality tutors are tutors who have high competence in learning and teaching activities, have tutors with minimum tertiary education qualifications.Key Words: Development Of Equal Tutor